UNIVERSUM KELEMBAGAAN KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) MODEL KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Ridwan Sya’rani; San Afri Awang; Nunuk Supriyatno; Ris Hadi Purwanto (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
This study aims to examine the relationship between the factors that forming the institutions in Production Forest Management Unit (KPHP) Model Banjar Regency, South Kalimantan Province. The analysis used is Structural Equation Model (SEM). SEM is a multivariate analysis were used to analyze the relationship between variables. The sampling technique was conducted using purposive sampling method with 83 respondents. Based on the results of the study showed that the institutionality is signiï€cantly inï€‚uenced by the factors of human resources, institutional variables and linkage.